(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The purpose of the present study was to investigate life stress and coping strategies of Chittagong university students. The sample of the study consisted of 120 university students of whom 60. students were first year (30 male and 30 female) and remaining 60 was masters (30 male and 30 female). Each group again consisted of 15 science students and 15 arts students. They were selected purposively from Chittagong University and some residential areas of Chittagong. The ·Bengali version of the "Life Stress Questionnaire" (Fahim 2001 ) and "coping scale" (Huque 2004) were used for investigating the life stress and coping strategies ·respectively. ·The obtained data were analyzed by using t-test. Results reveal that the life stress of masters’ students were greater than first year students (t=2.87, df= l 18,· p<0.05); the life stress of female students were more compared to the male students (t=2.07 ; - df= 118;: -p<0.05); the problem focused coping strategies of masters students were more compared to first year students (t=9.24; df=58, p<0.05); whereas the emotion focused coping strategies of first year were more compared to masters’ students; the problem focused coping strategies of male students were more compared · to female students ··strategies between male and female students and also there was no significant difference between science and arts faculties students in life stress and coping strategies. The Chittagong Univ. J. B. Sci. 8(1&2):37-50,203